2009
DOI: 10.1177/1352458508096680
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of adverse health behaviors in multiple sclerosis

Abstract: Patients with MS exhibit frequent adverse health behaviors, increasing the risk of other chronic diseases. Further research is needed to determine how these behaviors influence disability progression, quality of life, and other MS-related outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
79
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 41 publications
(53 reference statements)
12
79
0
3
Order By: Relevance
“…26 Smoking can also be associated with other comorbidities and with other environmental risk factors for MS, such as increased anti-Epstein-Barr virus antibodies. 26,27 Our exclusion criteria consisted of conditions that may influence quantitative MRI analysis, including cerebrovascular disease and positive history of alcohol abuse. However, we did not obtain data on other comorbidities, such as obesity, hypertriglyceridemia, and hypertension.…”
Section: Global and Central Atrophy Measuresmentioning
confidence: 99%
“…26 Smoking can also be associated with other comorbidities and with other environmental risk factors for MS, such as increased anti-Epstein-Barr virus antibodies. 26,27 Our exclusion criteria consisted of conditions that may influence quantitative MRI analysis, including cerebrovascular disease and positive history of alcohol abuse. However, we did not obtain data on other comorbidities, such as obesity, hypertriglyceridemia, and hypertension.…”
Section: Global and Central Atrophy Measuresmentioning
confidence: 99%
“…Indeed, persons with MS have similar rates of overweight and obesity as the general population [24,25], and this is problematic given the rates in the general population of adults [26]. For example, one study reported an average BMI of 27.0 kg/ m 2 in a large sample of persons with MS (n=8983); this average BMI value is comparable with the general population, but suggests that many persons with MS are overweight [25]. Another study of 123 women with MS reported that participants had higher BMI, waist circumference, and total body fat percentage than recommended by the World Health Organization [26] One limitation of previous research on deconditioning in persons with MS is that the studies measured single domains of physical fitness.…”
mentioning
confidence: 99%
“…These comorbid medical conditions, or the medications used to treat them, may have effects on the unborn child. Lifestyle factors such as smoking, alcohol intake, exercise and obesity may also play a role; for example, there is evidence that individuals with MS may be more likely to engage in behaviors that are known to be harmful to developing fetuses including smoking and alcohol consumption [42]. These potential confounders should be considered in any analysis of birth outcomes of individuals with MS.…”
Section: Potential Confounding Factorsmentioning
confidence: 99%